(untitled) (Kerala Journal of Psychiatry, 2022)
Background: Music-based interventions are currently being researched for their effectiveness in schizophrenia. Very few studies have been done in the acute phase. Further, there is a dearth of published Indian research in this context. Methods: A prospective, randomized, controlled, single-blind study was done in a tertiary psychiatric hospital in South India from October-2015 to March-2016. Immediately after admission, consenting adult patients with schizophrenia were randomly assigned to two groups. Over four weeks, Group-A(N=51) received 20 sessions of music-listening as an add-on to standard care, and Group-B(N=53) received standard care alone. Reduction in Positive and Negative Syndrome Scale (PANSS) scores and the drug dosage requirements for both groups were compared. Statistical analysis was done using two-way repeated-measures ANOVA for PANSS score reduction and Mann-Whitney U for drug dosage comparison. Results: We observed a greater decrease in PANSS scores in Group-A than Group B, but this difference did not reach significance (p>0.05 for all three subscales and total score). Group-A required lesser risperidone-equivalent doses than Group-B, but this was not significant (p=0.27). However, Group-A required significantly lesser diazepam equivalent (p=0.003) and trihexyphenidyl (p=0.007) doses than Group-B. Conclusions: The above findings suggest a possible additional benefit of adding music listening to standard care for the acute phase management of schizophrenia and reducing drug dosage requirements. Music-based interventions for schizophrenia warrant further research, especially in the Indian context and wider application in clinical practice.